1999
DOI: 10.1046/j.1365-2559.1999.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic microangiopathy in the small bowel

Abstract: This is the first report of diabetic microangiopathy in a bowel biopsy. The pathogenesis, specificity and significance of these angiopathic changes, controversies about diabetic microangiopathy in the gastrointestinal tract, and the association with hypertension are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…Impaired function of the vascular system then leads to ischemia, stroke and consequently hypoxia and neuropathy [137][138][139] . Because of their dominant clinical incidence, the diabetes-induced alterations in the capillary endothelium of retina [140][141][142][143] and renal glomerulus [144,145] have been the focus of a vast number of studies, while except for an early case report on microangiopathy in a bowel biopsy [146] , the impact of diabetes on capillaries within the intestinal wall has been almost completely overlooked until now. The myenteric ganglia are not vascularized; accordingly, the capillaries adjacent to the MP have the role to supply them.…”
Section: Endothelial Dysfunction In the Gut Wallmentioning
confidence: 99%
“…Impaired function of the vascular system then leads to ischemia, stroke and consequently hypoxia and neuropathy [137][138][139] . Because of their dominant clinical incidence, the diabetes-induced alterations in the capillary endothelium of retina [140][141][142][143] and renal glomerulus [144,145] have been the focus of a vast number of studies, while except for an early case report on microangiopathy in a bowel biopsy [146] , the impact of diabetes on capillaries within the intestinal wall has been almost completely overlooked until now. The myenteric ganglia are not vascularized; accordingly, the capillaries adjacent to the MP have the role to supply them.…”
Section: Endothelial Dysfunction In the Gut Wallmentioning
confidence: 99%
“…As early as 1965, it was shown that the arterioles and capillaries of the submucosa showed the same pathologic changes and thickening in long-term diabetes as the blood vessels of other organs [21]. Other studies could not verify vascular complications in the bowel mucosa [22], but mural thickening and luminal narrowing in blood vessels in duodenal biopsies have been described recently again [23]. However, this has not been discussed or further examined in relation to the etiology of gastrointestinal dysmotility.…”
Section: Discussionmentioning
confidence: 99%
“…When cardiovascular risk factors, cardiovascular diseases and associated treatments were specifically evaluated for their relationship to the development of colonic ischemia in a cohort of patients requiring admission due to an episode of ischemic colitis, diabetes mellitus (odds ratio (OR): 1.76, 95% CI: 1.001–3.077), dyslipidemia (OR: 2.12, 95% CI: 1.26–3.57), heart failure (OR: 3.17, 95% CI: 1.31–7.68), peripheral arterial disease (OR: 4.1, 95% CI: 1.32–12.72), and treatment with digoxin (OR: 0.27, 95% CI: 0.084–0.857) or acetylsalicylic acid (OR: 1.97, 95% CI: 1.16–3.36) were found to be independently associated with the development of ischemic colitis [15]. In diabetic patients, there is subepithelial collagenous thickening of colorectal mucosa along with basal membrane thickening and luminal narrowing in capillary vessels of the GI tract [16, 17]. These morphologic changes besides autonomic neuropathy-induced functional abnormalities in the mesenteric circulation may affect microvascular hemodynamics with deterioration of mesenteric microcirculation and development of colonic ischemia in the absence of major vessel occlusion.…”
Section: Discussionmentioning
confidence: 99%